Expediting Transition to Home Parenteral Nutrition With Fast-Track Cycling. (March 2017) - Austhof, Sandra I.; DeChicco, Robert; Cresci, Gail; Corrigan, Mandy L.; Lopez, Rocio; Steiger, Ezra; Kirby, Donald F.
Background. Delivery of home parenteral nutrition (PN) is typically cycled over 12 hours. Discharge to home on PN is often delayed due to potential adverse events (AEs) associated with cycling PN. The purpose was to determine whether patients requiring long-term PN can be cycled from 24 hours to 12 hours in 1 day instead of 2 days without increasing the risk of PN-related AEs. Methods. Hospitalized patients receiving PN at goal calories infused over 24 hours without severe electrolyte or blood glucose abnormalities were eligible. Patients were randomly assigned to a 1-step "fast-track" protocol or 2-step "standard" protocol. AEs were defined as hypoglycemia or hyperglycemia, new-onset or worsening dyspnea, tachycardia, tachypnea, lower extremity or sacral edema, pulmonary edema, or abdominal ascites and were graded as minor or major. Results. In the 63 patients studied, the most prevalent PN-related AE was hyperglycemia, occurring in 24.2% and 30.0% of patients in the fast-track and standard groups, respectively. Overall, there was no significant difference in the prevalence of PN-related minor AEs between fast-track and standard groups (33.3% and 53.3%, P = .5). No major PN-related AEs occurred in the fast-track group, while 1 major PN-related AE (pulmonary edema) occurred in the standard group. Conclusions. Fast-track cycling is as safe as standard cycling in patients without diabetes mellitus or major organ dysfunction requiring long-term PN. Fast-track cycling could potentially expedite hospital discharge, resulting in decreased healthcare costs and improved patient satisfaction.